Influence of Customer Service on the Performance of Hospitality Enterprises: Lessons from Sunbird Tourism Limited in Malawi - Sepulaand, Michael B.; Shirandula, Duncan (Online Science Journals, 2017)
This paper examines the influence of customer service on the success of hospitality enterprises. The paper argues that in order to deliver excellent services that will result into profitable hospitality business, there is need to bring into close alignment the understanding of customer service and its relationship to service customer relationship management (CRM), service quality and internal relationship marketing. If these aspects are carefully harnessed, they will result into a more delighted and satisfied customer, who will later become loyal to the hospitality business in the long run. If the service is consistently delivered to customer satisfaction, then this will eventually lead to increased and successful business performance. Aproposed conceptual framework showing the relationship among these elements has been provide. This paper is based on a document analysis of a 2015 annual report of Sunbird Tourism Limited (STL),the largest and leading operator in the hospitality industry in Malawi. A review of relevant and related literature on customer service and the related elements has been undertaken. The study has utilized secondary data for it was easy to link it to theory about the concepts. The findings of this study can therefore help hospitality operators in Malawi to appreciate the importance of embracing strategies that can inform the customer service and its influence onbusiness performance. The paper, however, recommends a thorough investigation of the validity of proposed conceptual framework in the country in order to gain insights into how customer service can truly influence the performance of a hospitality enterprise.
Keywords: Hospitality Industry; Customer Service; Service Quality; Internal Marketing; Customer Satisfaction; Customer Loyalty